Computers made easy : from dummy to geek - Bernstein, James ([United States] : [publisher not identified], 2023)
A Foundation in Computers & Software That's Easy to Understand. Computers Made Easy is designed to take your overall computer skills from a beginner to the next level, and beyond. This book will give you a top level understanding of how to use your PC without a needing a background in computers. This easy to use, step by step guide will help you navigate your way to becoming proficient with computers, operating systems (Windows 10 & 11), hardware and software.
Chapter 1 - What is a Computer? -- Chapter 2 - Computer Peripherals -- Chapter 3 - Microsoft Windows -- Chapter 4 - Software -- Chapter 5 - Printers -- Chapter 6 - The Internet -- Chapter 7 - Email -- Chapter 8 - Office Productivity Software -- Chapter 9 - Antivirus and Antispyware Software -- Chapter 10 - Avoiding Scams -- Chapter 11 - Error Messages, Crashes, & Troubleshooting -- Chapter 12 - Wi-Fi and Internet Troubleshooting -- Chapter 13 - Backup and Protection -- Chapter 14 - Security -- Chapter 15 - Cloud Storage -- Chapter 16 - Basic Networking.
Computers made easy :, Computers
Keywords: COMPUTER